2017
DOI: 10.1037/aca0000123
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the conceptual domain of aesthetic emotion terms: A pile-sort study.

Abstract: Aesthetic evaluations are often couched in terms of emotional impact; for example, an artwork may be deemed fascinating, moving, or surprising. Such emotional responses have been called “aesthetic emotions.” Given the broad variety of terms used to conceptualize emotional reactions to art and to other elicitors of aesthetic responses, the authors performed an exploratory study aimed at mapping the conceptual domain of such terms by using a pile-sort task. Seventy-five items designating emotional reactions duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 75 publications
4
33
0
Order By: Relevance
“…This decision is supported by the findings of [183] that happiness is clearly distinct from humor. Moreover, prior studies have revealed that, while positive emotions are in general less distinct from one another than negative emotions [155], there are important differences between joy and amusement [184].…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…This decision is supported by the findings of [183] that happiness is clearly distinct from humor. Moreover, prior studies have revealed that, while positive emotions are in general less distinct from one another than negative emotions [155], there are important differences between joy and amusement [184].…”
Section: Resultssupporting
confidence: 68%
“…In particular, we considered a study [183] on the conceptual space of the aesthetic emotion terms that were also included in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these approaches were entirely theoretical and could therefore not be applied as psychometric models of emotions. Finally, emotions were assessed as part of networks in psychopathology research (e.g., Bringmann et al, 2016;Pe et al, 2015;Van de Leemput et al, 2014), attitudes (Dalege et al, 2016(Dalege et al, , 2017, aesthetics (Hosoya et al, 2017), and personality (e.g., Pavani, Le Vigouroux, Kop, Congard, & Dauvier, 2017), and mixed emotions were investigated with the help of co-occurrence networks of emotions (e.g., Moeller, Ivcevic, Brackett, & White, 2018). However, in these studies, emotions were treated as single variables and not conceptualized via the causal interaction of multiple emotion components as we propose.…”
Section: Discussionmentioning
confidence: 99%